Analisis Fatwa Jabatan Mufti Wilayah Persekutuan Malaysia Irsyad Al-Fatwa Ke 94 dengan Fatwa Majelis Ulama Indonesia Nomor 6 Tahun 2009 Tentang Otopsi Jenazah - Hamdani, Mohd Asrul; Syafa’at, Abdul Kholiq (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2021)
Autopsy is still unacceptable in the Islamic community. It is considered an act that hurts and destroys a corpse and also against Islamic law. The problem in this research is how the legal istinbāṭ method of autopsy for bodies according to the position of the 94th Mufti of the Malaysian Alliance Region Ersyad Al-Fatwa and the Fatwa of the Indonesian Ulama Council Number 6 of 2009 and how to compare the Position of the Mufti of the Malaysian Alliance Region, Irsyad Al-Fatwa 94 with the Fatwa of the Indonesian Ulema Council on legal istinbāṭ for autopsy bodies? This study is comparative study. The results, the Malaysian Association of Territory Mufti has determined that initially, it is legal to carry out an autopsy of a corpse to be permissible. Then it is legal to autopsy a body based on certain circumstances. The Indonesian Ulama Council also enforces the law on the autopsy of bodies as it must be based on certain circumstances. In a situation where a corpse autopsy is performed in order to save a still-living fetus in the womb of the corpse, it is mandatory.